2018
DOI: 10.1144/pygs2017-004
|View full text |Cite
|
Sign up to set email alerts
|

Miospores from the Brigantian stratotype section at Janny Wood, Cumbria

Abstract: Miospores from the clastic intervals between the Robinson Limestone and the Peghorn Limestone in the Brigantian (Mississippian) stratotype section at Janny Wood, Cumbria, are assigned to the Tripartites vetustus–Rotaspora fracta (VF) Assemblage Biozone. The species Murospora parthenopia , normally considered to be restricted to the underlying Raistrickia nigra–Triquitrites marginatus (NM) Biozone, is also recorded. Tripartites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Nevertheless, those taxa can be rarely recorded from the late Asbian (Waters et al 2017a, b). McLean et al (2018) analysed the miospore assemblages in the basal Brigantian stratotype section at Janny Wood, and suggested that the VF zone should be situated at a level below the shales between the Robinson and Birkdale Limestone, or even older, in the latest Asbian. Ingrams et al (2020) recorded the NM zone in the Woodend Limestone; however, the occurrence of this biozone in the early Brigantian is not unusual (Cózar et al 2006).…”
Section: Northumberland Coastmentioning
confidence: 99%
“…Nevertheless, those taxa can be rarely recorded from the late Asbian (Waters et al 2017a, b). McLean et al (2018) analysed the miospore assemblages in the basal Brigantian stratotype section at Janny Wood, and suggested that the VF zone should be situated at a level below the shales between the Robinson and Birkdale Limestone, or even older, in the latest Asbian. Ingrams et al (2020) recorded the NM zone in the Woodend Limestone; however, the occurrence of this biozone in the early Brigantian is not unusual (Cózar et al 2006).…”
Section: Northumberland Coastmentioning
confidence: 99%
“…In 2004, the IUGS International Subcommission on Carboniferous Stratigraphy recognised the Viséan as the formal international stage, and thus, the Holkerian became a formal regional substage (Heckel and Clayton 2006). As with many other British substages of the Viséan since their definition in 1976, subsequent revision of stratotypes have raised problems and inconsistencies (Simpson and Kalvoda 1987, Riley 1993, 1994, Cózar and Somerville 2004, Aretz and Nudds 2005, McLean et al 2018. The base of the Holkerian at Barker Scar represents the last of the Viséan stratotype sections to be investigated and revised (Cózar et al 2022).…”
Section: The British Holkerian Substagementioning
confidence: 99%
“…As mentioned above, many shaley facies in the upper part of the studied succession could be only dated using miospore zones, and hence, there is an important issue concerning the correlation of the base of the NC zone. For some authors, the base of this zone should be correlated with the P 2b ammonoid subzone (e.g., George et al, 1976; Owens et al, 2004; Waters et al, 2011), whereas for others, it should be correlated with intermediate levels of the P 1a subzone (Sevastopulo & Wyse Jackson, 2009), or its base should be correlated with the base of the P 2a subzone (McLean et al, 2018). Miospore details in Owens et al (2004) and Owens, McLean, Simpson, Shell, and Robinson (2005) suggest that the NC zone occurs in shales associated with the St Monans Little Limestone and Second Abden Limestone in Fife, Scotland and the Five Yard Limestone in northern England, and thus, the correlation with the P 2b zone is followed here (Figure 2).…”
Section: Criteria For the Definition Of The Serpukhovian Stage And Sumentioning
confidence: 99%
“…For the correlation with the ammonoid and miospore zones, the biozones of those fossil groups recognized in the Alston Block are adopted here, based on data in Owens, McLean, and Bodman (2004), Brand (2011), Waters, Somerville, Stephenson, Cleal, and Long (2011), Waters, Millward, andThomas (2014), andMcLean (2018). As mentioned above, many shaley facies in the upper part of the studied succession could be only dated using miospore zones, and hence, there is an important issue concerning the correlation of the base of the NC zone.…”
Section: Criteria For the Definition Of The Serpukhovian Stage And mentioning
confidence: 99%